2020
DOI: 10.1111/gcb.15068
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of trophic interactions increases the vulnerability of an alpine butterfly species to climate change

Abstract: Climate change is expected to have significant and complex impacts on ecological communities. In addition to direct effects of climate on species, there can also be indirect effects through an intermediary species, such as in host-plant interactions.Indirect effects are expected to be more pronounced in alpine environments because these ecosystems are sensitive to temperature changes and there are limited areas for migration of both species (i.e. closed systems), and because of simpler trophic interactions. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 63 publications
(84 reference statements)
1
32
0
Order By: Relevance
“…Nevertheless, previous studies showed similar range shifts towards higher altitudes in high mountain systems also for other organismal groups, as reported for montane and subalpine bumblebees, with upwards shift of more than 300 m within 33 years 35 , or a shift of almost 500 m of the alpine bumblebee Bombus alpinus in the Alps within as little as three decades 36 . Similarly, mountain plant species (the larval food plants of many butterflies) have shifted their distributions considerably towards the summits over time 37 , which might also interrupt interactions among species 38 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, previous studies showed similar range shifts towards higher altitudes in high mountain systems also for other organismal groups, as reported for montane and subalpine bumblebees, with upwards shift of more than 300 m within 33 years 35 , or a shift of almost 500 m of the alpine bumblebee Bombus alpinus in the Alps within as little as three decades 36 . Similarly, mountain plant species (the larval food plants of many butterflies) have shifted their distributions considerably towards the summits over time 37 , which might also interrupt interactions among species 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Filazzola and colleagues predict a potential distribution expansion of this butterfly in the wake of climate warming. However, by integrating the future distributions of the relevant Sedum species (under dry-climate scenarios), a relevant reduction of the realised distribution of the butterfly is more likely in the near future 38 . Severe future geographic mismatches between butterflies and their larval food plants become even more likely against the background of diverging response velocities in both groups: The response of plant species to climate warming is rather moderate and slow if compared with flying insects 40 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…cresphontes at a broad scale. While other factors were not tested here, for example, biotic interactions (e.g., host plant occurrence; Filazzola et al., 2020), our results suggest that P . cresphontes depends on specific heat accumulation and water availability to complete its life cycle.…”
Section: Discussionmentioning
confidence: 62%
“…Non‐mobile life stages of insects, such as eggs, are particularly vulnerable to weather extremes compared to mobile caterpillars (Turlure et al 2010) and adults (Ashton et al 2009, Bennett et al 2015) which can effect some choice in microclimate when active in spring and summer. Temperatures experienced by over‐wintering butterflies affects their physiology (Williams et al 2012, Stuhldreher et al 2014), dynamics (Forister et al 2011, Boggs and Inouye 2012, Roland and Matter 2013, 2016), community structure (Nice et al 2014) and potentially changes in their geographic range (Crozier 2004, Filazzola et al 2020).…”
Section: Discussionmentioning
confidence: 99%